Анализ хозяйственной деятельности совхоза - Дормидонтов Михаил Петрович (Колос, 1974)
Экземпляры: КХ (20101010) / Инвентарный номер: 575099 / Цена: 0.50 / Сис.шифр: 65.9(2)321.1 / Авт.знак: Д 68 / ГРНТИ: 68 / ББК: 65.321.1